The closing of open minds: Need for closure moderates the impact of uncertainty salience on outgroup discrimination. (26th September 2015) - Brizi, Ambra; Mannetti, Lucia; Kruglanski, Arie W.
Abstract : In three studies, we examined how dispositional need for cognitive closure (NCC) moderates the impact of various types of uncertainty salience (personal and supraliminal in studies 1 and 2; economic and subliminal in Study 3) on implicit attitudes (studies 1 and 3) and explicit discriminatory intentions (Study 2) towards outgroup members. Across all three studies, we found that uncertainty increased discrimination against outgroups among low‐NCC individuals but not among high‐NCC individuals. High‐NCC individuals tended to be more discriminatory irrespective of uncertainty salience. These results suggest that uncertainty salience leads individuals with a low dispositional need for closure to act like those with high need for closure. The implications of the findings for theories about how uncertainty influences social attitudes and intergroup behaviour are discussed.